Encapsulation of Perovskite Solar Cells for High Humidity Conditions - Dong, Qi; Liu, Fangzhou; Wong, Man Kwong; Tam, Ho Won; Djurišić, Aleksandra B.; Ng, Annie; Surya, Charles; Chan, Wai Kin; Ng, Alan Man Ching (ChemSusChem, 2016)
Invited for this month′s cover is the group of Aleksandra B. Djurišić at the University of Hong Kong along with collaborators from the University of Hong Kong, Hong Kong Polytechnic University, and South University of Science & Technology of China. The image shows outdoor testing performance of perovskite solar cells during summer in Hong Kong. The Full Paper itself is available at 10.1002/cssc.201600868. “In the early years, organic optoelectronics were facing similar criticism concerning stability issues, yet there are now commercial organic displays. One of the key issues was encapsulation…” This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201600868. View the Front Cover here: 10.1002/cssc.201601091.